Produção de alimentos, agricultura camponesa e soberania alimentar: o PAA no estado de Goiás - Ângela Maria Martins Peixoto; Adriano Rodrigues de Oliveira (Confins)
This text is centered on assessing the progression and crisis of the Food Acquisition Program (PAA) in Brazil, especially in the state of Goiás, during the current context of budget constraint. The analysis is based on literature and document review as well as data from secondary and primary sources, with which maps and tables were generated. During PAA’s first ten years of operation, the institutional markets created fostered the commercialization of food from peasant agriculture in achieving of food and nutritional security. However, the program is now institutionally threatened while food insecurity in the country is increasing.